Imbalance in Renal Vasoactive Enzymes Induced by Mild Hypoxia: Angiotensin-Converting Enzyme Increases While Neutral Endopeptidase Decreases - Vio, Carlos P.; Salas, Daniela; Cespedes, Carlos; Diaz-Elizondo, Jessica; Mendez, Natalia; Alcayaga, Julio; Iturriaga, Rodrigo (Frontiers in Physiology, 2018)
Chronic hypoxia has been postulated as one of the mechanisms involved in salt-sensitive hypertension and chronic kidney disease. Kidneys have a critical role in the regulation of arterial blood pressure through vasoactive systems, such as the renin-angiotensin and the kallikrein-kinin systems, with the angiotensin-converting enzyme and kallikrein being two of the main enzymes that produce angiotensin II and bradykinin, respectively. Neutral endopeptidase 24.11 or neprilysin is another enzyme that among its functions degrade vasoactive peptides including angiotensin II and bradykinin, and generate angiotensin 1-7. On the other hand, the kidneys are vulnerable to hypoxic injury due to the active electrolyte transportation that requires a high oxygen consumption; however, the oxygen supply is limited in the medullary regions for anatomical reasons. With the hypothesis that the chronic reduction of oxygen under normobaric conditions would impact renal vasoactive enzyme components and, therefore; alter the normal balance of the vasoactive systems, we exposed male Sprague-Dawley rats to normobaric hypoxia (10% O2) for two weeks. We then processed renal tissue to identify the expression and distribution of kallikrein, angiotensin-converting enzyme and neutral endopeptidase 24.11 as well as markers of kidney damage. We found that chronic hypoxia produced focal damage in the kidney, mainly in the cortico-medullary region, and increased the expression of osteopontin. Moreover, we observed an increase of angiotensin-converting enzyme protein in the brush border of proximal tubules at the outer medullary region, with increased mRNA levels. Kallikrein abundance did not change significantly with hypoxia, but a tendency toward reduction was observed at protein and mRNA levels. Neutral endopeptidase 24.11 was localized in proximal tubules, and was abundantly expressed under normoxic conditions, which markedly decreased both at protein and mRNA levels with chronic hypoxia. Taken together, our results suggest that chronic hypoxia produces focal kidney damage along with an imbalance of key components of the renal vasoactive system, which could be the initial steps for a long-term contribution to salt-sensitive hypertension and chronic kidney disease.